PENDAMPINGAN DAN PELATIHAN MEDIA PROMOSI PADA HOME INDUSTRY PANGAN - Hery Widijanto; Zulaikhati Rahma; Kournikova, Syarifa Anna; Mely Valentina; Nur Rizky Adi Pamungkas (Inisiasi, 2024)
Public service with the theme 'supervision and promotion of the home industries' in Giriwoyo kelkelity' is aimed at increasing the knowledge and ability of the umkm's most important food industry in Giriwoyo families' garrisoning, advertising, and marketing of food products. Methods of approach are used to introduce the Canva application as a means of media promotion to the umkm home industry. The research phase includes coordination and data collection, standardized packaging labels, and promotional media production. Results show that while all participants present have used packaging and labeling of foodstuffs, they still have been found to be non-standard delivery. In addition, the home industry's leading stakeholders have also acquired digital media outlets to release their products through social and print media. It is a continuing effort to encourage communities more towards the home industry to increase its product capabilities, strengthen the value propositions of products and services offered, and increase public purchasing power to sustain the sustainability of the digital age.